PENERIMAAN PBB-P2 SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH - Zawil Fitra; Tri Sukirno Putro; Lena Farida (JIANA ( Jurnal Ilmu Administrasi Negara ), 2017)
Admission of P2 and its Contribution to Local Original Income. This study aims to find out and analyze the implementation of PBB P2 organized by the Dumai City Revenue Service in terms of policy aspects, administrative aspects and financial aspects, the development of PBB revenue P2 and its contribution to the Original Revenue. This study used descriptive qualitative method. The research informant is the head and staff of the Dumai City Revenue Service. Data collection techniques are interviews, questionnaires and documentation. Methods of data analysis using performance measurement analysis with the approach of PBB PBB amount P2 with approach of policy aspect, administration aspect and financial aspect. The results show that the largest contribution of PBB-P2 to local taxes began in 2013 and 2014.